Power Relation and White-Collar Crime: Case Study of Coastal Reclamation in Indonesia - Kurniawan, Dedy Anung; Dermawan, Mohammad Kemal; Simon Runtrambi, Arthur Josias (International Journal of Criminology and Sociology, 2021)
This research aims to understand the power relation and white-collar crime on managing the coastal reclamation and its implication in Indonesia that is very significant at the ontological and sociological level. The problem is very interesting to be analyzed by conducting a qualitative research method based on power theory and crime theory. Data were collected through in-depth interviews, observation, and documentation related to coastal reclamation and its implication in Indonesia. Data were analyzed by using interactive models are data reduction, data display, data verification, and supported by triangulation. The results were based on ontological and sociological levels using criminology perspective for understanding the coastal reclamation and its implication in Indonesia that are needed for providing information to stakeholders related to the regulations and sanctions. This result provides inputs for making better regulation on coastal reclamation policy in Indonesia for state agencies as public officials and practitioners.